2000
DOI: 10.1080/02839310050162352
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Patients' Perspectives, Staff's Documentation and Reflections on Basic Nursing Care

Abstract: In recent years, Denmark has witnessed an increasing written and oral debate concerning the quality of basic nursing care. The present study is an attempt to characterize basic nursing care in a Danish hospital by collecting data on patient perceptions of their main somatic problems in seven pre-set categories. These data include documentation of patient problems in corresponding problem categories, and the staff's additional knowledge about patient problems. Triangulation of methods was used. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 18 publications
2
42
2
Order By: Relevance
“…RNs and patients stated the same level of importance of attending to problems 44% of the time. In sharp contrast, other studies have reported RNs’ recognition of patient‐perceived problems with 70% agreement or better (Adamsen & Tewes 2000, Hansen et al. 2002).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…RNs and patients stated the same level of importance of attending to problems 44% of the time. In sharp contrast, other studies have reported RNs’ recognition of patient‐perceived problems with 70% agreement or better (Adamsen & Tewes 2000, Hansen et al. 2002).…”
Section: Discussionmentioning
confidence: 69%
“…Nurses and patients in somatic settings have been found to hold different opinions about the presence of nursing problems (Farrell 1991, Adamsen & Tewes 2000). In general, nurses overestimated their patients’ nursing problems, with emotional problems being overestimated more often than physical ones (Farrell 1991, Löfmark et al.…”
Section: Introductionmentioning
confidence: 99%
“…Documentation of expressions of decreased wellbeing perceived by HCPs in their communication with patients is an important piece of the puzzle, as it forms a basis both for decisions and for understanding the patient's overall health situation (Adamsen & Tewes , Langewitz et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pieces of research have suggested that the patient's perspective should be an important prerequisite for describing and prioritizing the patient counselling practices of health professionals [5][6][7][8][9][10][11], the reason being that patients' perspectives on illness and medicine use often differ from those of health professionals [8,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%